La Tinta Bay, Trinidad, B.W.I. - (:unkn) unknown (Waterman, Hatter, Clothier and Outfitter,[Trinidad and Tobago], 2011)
The postcard shows La Tinta Bay, a popular beach on the island of Chacachacare, the westernmost of the Bocas Islands which belong to Trinidad and Tobago.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Islands--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Chacachacare